Adult Education in German-speaking Countries and Perspective Directions of its Development in Ukraine - Nelina Khams’ka; Dmytro Matiiuk (Pedagogical Discourse, 2018)
The importance of lifelong learning is explained in the article. The main ideas of the Conception of adult education in Ukraine are highlighted.The aim of this research is to analyze the activity of educational institutions in German-speaking countries, that support the development of lifelong learning, and to find perspective directions of education throughout life improvement in Ukraine. Achievement of the suggested aim involves the use of a set of methods: historically-structural in order to sort out pedagogical literature and to represent historiography of this problem; comparative in order to single out organizational and technological aspects of adult education development in Ukraine; extrapolation – for studying the tendencies of lifelong learning development in German-speaking countries and their creative transfer to the Ukrainian educational space. In the course of our research we have analyzed the preconditions of adult education development in German-speaking countries. The main institutions, that support the development of lifelong learning in German-speaking countries, are singled out: Bundesinstitut für Berufsbildung, Deutsches Institut für Erwachsenenbildung, der Deutsche Volkshochschulverband, Deutsche Gesellschaft für wissenschaftliche Weiterbildung und Fernstudium. The studying of the adult education development in German-speaking countries has given us an opportunity to highlight perspective directions of extrapolation into Ukrainian educational system. They are the following: creation of the adult education institute network vertically – from central educational institutions to regional and local; development of conceptual foundations of this lifelong education level, specification of  content, forms, methods and learning tools of adult education; implementation of innovative projects, that would provide access of adults to different forms of lifelong learning and would give an opportunity to deepen knowledge and improve professional competence without leaving the working place. Discussions concerning adult’s motivation to lifelong learning are analyzed. It was concluded that the development of adult education system and its implementation in Ukraine based on progressive experience of German-speaking countries will ensure personal and professional growth of every citizen of Ukraine and will contribute to the knowledge society formation.